2002
DOI: 10.4049/jimmunol.168.4.2054
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Sm Autoantibodies in Systemic Lupus Target Highly Basic Surface Structures of Complexed Spliceosomal Autoantigens

Abstract: Autoantibodies directed against spliceosomal proteins are a common and specific feature of systemic lupus erythematosus. These autoantibodies target a collection of proteins, including Sm B, B′, D1, D2, and D3. We define the common antigenic targets of Sm D2 and D3 and examine their role in spliceosomal autoimmunity. Our results define nine major common epitopes, five on Sm D2 and four on Sm D3. These epitopes have significantly higher (more basic) isoelectric points than do nonantigenic regions. In fact, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 37 publications
1
55
0
Order By: Relevance
“…Sequences with multiple lysine residues have been shown to be very antigenic in the nRNP 70K molecule, whereas epitopes containing multiple arginine residues have been demonstrated to be highly antigenic in the Sm D1 protein. Additionally, a high isoelectric point has proven to be a fair indicator of autoantigenicity of epitopes in the snRNP spliceosomal system (35), and both the A3 and A6 peptides have relatively basic pIs (12.0 and 11.0, respectively). The difference is not due to species specificity, because we have demonstrated that the sequences of the epitopes in question are identical between human and rabbit.…”
Section: Discussionmentioning
confidence: 99%
“…Sequences with multiple lysine residues have been shown to be very antigenic in the nRNP 70K molecule, whereas epitopes containing multiple arginine residues have been demonstrated to be highly antigenic in the Sm D1 protein. Additionally, a high isoelectric point has proven to be a fair indicator of autoantigenicity of epitopes in the snRNP spliceosomal system (35), and both the A3 and A6 peptides have relatively basic pIs (12.0 and 11.0, respectively). The difference is not due to species specificity, because we have demonstrated that the sequences of the epitopes in question are identical between human and rabbit.…”
Section: Discussionmentioning
confidence: 99%
“…One microgram of Sm, nuclear RNP (nRNP), Ro, or La (ImmunoVision, Springdale AR) per well was plated. These methods have been previously described in detail (20,21). Anti-dsDNA antibodies were screened with a solid-phase assay (Varelisa; Pharmacia & Upjohn, Freiburg, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…In epitope-mapping studies, several linear and conformational epitopes have been mapped on the SmB and D proteins (1,7,9,12,14,17,19). On SmD1 and BBЈ, the major reactivity was predominantly found in the C-terminal extensions (7,8,19).…”
mentioning
confidence: 99%